Penatalaksanaan Holistik Pada Pasien Laki-Laki Usia 54 Tahun dengan Gout Artritis dan Hipertensi Melalui Pendekatan Kedokteran Keluarga di Puskesmas Sumur Batu - Attara Rafilia Adhata; Ernawati, Tutik (Medula, 2025)
Gout arthritis is a chronic progressive disease caused by the deposition of monosodium urate (MSU) crystals in the joints, kidneys and other connective tissues due to hyperuricemia. Based on the 2016 Bandar Lampung City health profile, hyperuricemia was included in the 10 most common diseases 141,857 cases. Hypertension is a condition when blood pressure is more than 140/90 mmHg. According to WHO, hypertension is a major problem that attacks 22% of the world's population. The purpose of this case report is to Identify internal risk factors, external risk factors, and clinical problems in patients. Implementing Evidence Based Medicine-based family doctor services for patients and patient management based on a framework for solving patient problems with a patient centered, family focused and community oriented approach. This study is a case report study. Primary data were obtained through history taking (autoanamnesis from the patient and alloanamnesis from the patient's family), physical examination and home visits. Secondary data were obtained from the patient's medical record. Assessment is based on a holistic diagnosis from the beginning, process, and end of the study qualitatively and quantitatively. Patient Mr.MY is 54 years old, has been diagnosed with gout arthritis and hypertension has concerns about his complaint is getting worse and cant be cured. The patient's hope is that the complaints disappear completely and do not recur. The patient's limited knowledge of the illness and an unfavorable lifestyle are factors that cause problems that occur in patients and their families. The diagnosis of gout arthritis and in this case is in accordance with several theories and critical studies from recent research. Management has been given in accordance with the management guidelines. There is good progress in patients starting from decreased clinical symptoms to changes in behavior after an intervention based on evidence-based medicine that is family-approach and patient-centered.